Human Temperature Control A Quantitative Approach - Wissler, Eugene H. (Springer Berlin Heidelberg, 2018)
The principal objective of this book is to provide information needed to define human thermal behavior quantitatively. Human thermal physiology is defined using mathematical methods routinely employed by physicists and engineers, but seldom used by physiologists. Major sections of the book are devoted to blood flow, sweating, shivering, heat transfer within the body, and heat and mass transfer from skin and clothing to the environment. Simple algebraic models based on experimental data from a century of physiological investigation are developed for bodily processes. The book offers an invaluable source of information for physiologists and physical scientists interested in quantitative approaches to the fascinating field of human thermoregulation.